An Unusual Case of Colon Perforation Complicating Acute Pancreatitis - Aghenta, Anthony A. (S. Karger AG, 2009)
Colonic complications of severe acute pancreatitis occur rarely. Although there have been several theories on how pancreatic pseudocysts rupture into the colon, the exact pathogenesis remains unknown. We report an unusual case of pseudocysts complicating severe acute pancreatitis presenting with colonic perforation in a 71-year-old man with a history of chronic mesenteric ischemia. Pressure effects from a giant pseudocyst and intravascular volume depletion with acute insult on chronic mesenteric ischemia are highlighted as possible etiologic factors.